Failure Evaluation of Thermal Spray Coating Using High-Velocity Oxy-Fuel (HVOF) on Steam Turbine Shaft 940-PT 2 A/B - Siregar, Banuaran Ibrahim; Nasution, Ahmad Kafrawi; Istana, Budi (Journal of Applied Materials and Technology, 2024)
The repair of worn steel shaft surfaces in power transmission systems is made possible by thermal spray procedures, which have become an essential technology in many sectors. With this novel approach, worn shaft components may be recycled effectively since an API 687-compliant wear-resistant coating designed for specialty rotating equipment repairs is applied. The process's efficacy stems from its capacity to extend the functional life of essential mechanical components, therefore decreasing replacement expenses and downtime. The variety of factors that affect the result highlights the intricacy of thermal spray techniques. Finding the ideal mix of these crucial process variables becomes essential to provide the required degree of wear resistance. The coated shafts perform better as a result of this careful tuning, which also guarantees dependability under challenging working conditions. The coated shafts' surface hardness data in this investigation showed that the initial coating hardness value was below the predetermined goals. Several parts that interact with the shaft were redesigned strategically in response to these discoveries. These adjustments were mainly motivated by economic considerations, to optimize effectiveness while resolving the noted hardness deficiencies. Furthermore, a thorough analysis of failure data showed important correlations between different operational parameters and how they interacted, offering a further understanding of how these factors affected wear resistance. This research allowed for the identification of crucial parameters that required change and emphasized the precise balance essential for optimum thermal spray application. All things considered, this study emphasizes how critical it is to use a methodical approach to improve thermal spray processes, guarantee successful shaft component restoration, and ultimately increase the operational longevity of such components in challenging applications.